Awareness, Knowledge and Willingness Regarding Eye Donation among Dental Students of Kist Medical College and Teaching Hospital, Lalitpur, Nepal - Basnet, Anjila; Basnet, Pragya Singh; Lamichhane, Ram Sudhan; Shrestha, Prabhat (Journal of Chitwan Medical College, 2019)
Background: Corneal disease constitutes a significant cause for visual impairment and blindness in the developing world. Visual rehabilitation by corneal transplantation for which increased awareness regarding an eye donation is essential, remains the only treatment option for restoring sight in those who suffer from corneal blindness. Hence, the present study conducted to assess the awareness, knowledge and willingness about eye donation among dental students of KIST medical college & teaching hospital, Nepal Methods: A cross-sectional study was carried out in KIST medical college and teaching hospital in Nepal during the period of 21st to 30th April 2019. A total of 185 dental students were selected as study group by convenience sampling technique. A Semi-structured questionnaire was used for data collection and analyzed by using SPSS 16. Descriptive statistics and Chi square/ Fischer exact tests were used for data analysis. Results: Out of total 185 dental students who participated in this study, 176 (95.1%) were aware about eye donation, 133 (71.9%) knew that the cornea is used for eye donation and 70 (37.8%) knew that ideal time for eye donation is within six hours of death. Awareness regarding eye donation in male and female students was found to be statistically significant (p =0.013). Conclusions: The present study revealed that most of the dental students were aware regarding eye donation and most of them were willing to donate their eyes. Awareness regarding eye donation will form the prime base for the elimination of avoidable corneal blindness in Nepal.